Formation, control and functionalization of nanoporous silver through changing dealloying media and elemental doping - Ji, Hong; Wang, Xiaoguang; Zhao, Changchun; Zhang, Chi; Xu, Junling; Zhang, Zhonghua (CrystEngComm, 2011)
In this paper, the influence of alloy composition, dealloying solution and elemental doping on the dealloying process of rapidly solidified Mg-Ag based alloys and the formation of nanoporous silver (NPS) has been investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The results show that NPS and nanoporous silver-palladium (NPS-Pd) alloys can be fabricated by dealloying the Mg-Ag based alloys in acid media under free corrosion conditions. The NPS and NPS-Pd exhibit an open, three-dimensional bicontinuous interpenetrating ligament-channel structure. Furthermore, alloy composition and phase constitution of the Mg-Ag precursors have a significant influence on the ligament/channel size and the formation of cracks in NPS. The length scales of ligaments/channels in NPS can be tuned by simply changing the dealloying solution. Crack-free NPS with good mechanical integrity and small ligament/channel sizes can be obtained by dealloying the Mg-Ag alloys in suitable acid solutions. Moreover, the addition of Pd into Mg-Ag has a significant influence on the dealloying process and results in the formation of ultrafine bimodal NPS-Pd with ligaments/channels of ∼5 nm. The NPS-Pd alloy shows excellent hydrogen sensing properties with stable sensitivity, fast response and low detection limit. Our present findings provide implications for control and functionalization of nanoporous metals or alloys by alloy design, selection of dealloying media and elemental doping. Formation, control and functionalization of nanoporous silver and its alloys can be realized by alloy design, changing dealloying solutions and elemental doping.